ACTIVITIES OF SHELL PETROLEUM DEVELOPMENT COMPANY IN THE OIL PRODUCING AREA OF NIGERIA: A STUDY OF THE OGONI YOUTH RESTIVENESS - Muhammad, Buba Amne (BW Academic Journal, 2022)
The youths in the Niger Delta of Nigeria had been deprived by their leaders of the oil money accruing to their states. Hence youths had to take arms, gone on kidnapping of foreign oil workers; the indigenes and killing of the security forces. Shell Nigeria, otherwise known as Shell Petroleum Development Company has been widely condemned for human right abuses, including its conniving with Nigerian authorities for the mass murder in the community, impoverished the people of the community sources of livelihood. (Anyaegbunam, 2000).It is the belief of this study that oil companies must learn from the fate that has befallen Shell in Ogoni land. Therefore the study will attempt an analysis of what has transpired in the Niger Delta area, including the treacherous activities of government officials in the area. The study will use both qualitative and quantitative methods for data collection and analysis. The oil companies, the Federal Government, Leaders and youths of the delta areas must come to terms with the realities of the day and do justice to each other, so that peace and stability could prevail. (Buba,2014).